(untitled) (Global Journal of Management and Business Research, 2018)
The main objective of the study is to see the role of Battery Operated Rickshaw (BOR) in urban income and employment in Chittagong city. Data are collected from 151 battery operated rickshaw drivers from 10 selected study areas in Chittagong City. Maximum rickshaw drivers (40%) having the income range TK. 15000-19999. It is revealed from our analyses that 53.57% battery rickshaw owners bear purchasing cost of Tk. 23000-25999. 89.40% drivers save less amount of money. From the study it is clear that 65% battery rickshaw owners bear repairing cost less than TK. 5000. 28.57% battery operated rickshaw owner can gain profit of Tk. 11000-15999, whereas 42.86% can earn profit of Tk. 6000-10999. Study reveals that battery operated rickshaw drivers earn two times more than their previous occupation. 46% rickshaw drivers choose this profession for their comfort. The important implication of the study is that if Chittagong City Corporation (CCC) can reintroduce battery operated rickshaw considering some issues, it also helps to decrease unemployment.